Synthesis and Immobilization of Benzothiazole‐Appended Triazole‐Silane: Biological Evaluation and Molecular Docking Approach. Issue 5 (6th February 2018) - Singh, Gurjaspreet; Chowdhary, Kavita; Satija, Pinky; Singh, Akshpreet; Singh, Baljinder; Singh, Kashmir; Espinosa, Cristóbal; Esteban, M. Angeles; Sehgal, Rakesh; Verma, Vikas
Abstract: The present work involves the synthesis of Benzothiazole capped triazole‐silane(3) by 'Click Silylation' and its immobilization onto silica surface. This new silane is characterised by IR, 1H, 13C spectroscopy. TGA, TEM and SEM were the evidence for its adsorption at silica surface. The anti‐parasitic, anti bacterial and anti oxidant activity of synthesised compounds was evaluated. The results shows that nanoparticle of silane displayed more significant activity as compared to benzothiazole derived silane (3) against G. lamblia, T. vaginalis, various bacterial strains (E.coli, Bacillus subtillus, Staphylococcus aureus, Vibrio cholera) and showed potential anti‐oxidant activity. Further Molecular docking study was performed to analyse the binding manner and enzyme inhibitory activity of compound‐3 with β‐glucuronidase. Abstract : The current study involves modification of benzothiazole moiety with triazole and silane part by 'Click Silylation' approach. This was followed by immobilization of the product onto the silica surface. The articles also assess antiparasitic, antibacterial and antioxidant activity of the synthesized compound and its nanopartices. Further the binding manner and enzyme inhibitory activity of compounds with β‐glucuronidase has been studied using Molecular docking analysis.